(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
This symposium discusses evidence-based strategies for integrating PA into health frameworks, highlighting challenges, policy implications, and future directions for a more physically active world. The contributions, including diverse and innovative PA programmes for older adults in communities, provide unique insights on development and implementation with a focus on policy aspects and a fruitful basis for deeper discussions with the audience. The “Movement Inspired by Martial Arts” (MIMA) programme to support PA and healthy ageing in diverse and socially disadvantaged communities was developed in a co-production process by a diverse group of stakeholders in Cardiff. It targets coordination and strength and includes educational materials, group sessions, and structured social interaction. Volunteer MIMA ambassadors are trained to help sustain and disseminate the programme. In collaboration with the Finnish Gymnastic Federation, the national Older People on the Move Programme (OPMP) has designed and conceptualised adapted artistic gymnastics for older adults. The concept includes a guide, instructional videos, and instructor training and is freely available. After completing the training, participants implement the activities locally. Another Finnish programme targets the training of professional sport instructors. It aims to enable the professionals to locally train and support volunteers to act as peer instructors for exercise groups and outdoor friends. A survey was sent to these volunteers to examine their motivations and perceived benefits of the activities. The Swiss contribution aims at the self-management programme “Living well with COPD” to support people with the chronic obstructive pulmonary disease (COPD) in managing their disease and adopting healthy lifestyle behaviours, including increasing physical activity. The evaluation of the nationwide implementation showed the significance of incorporating physical activity into patient education. The final contribution includes a Joint Statement proposing a coordinated, forward-looking strategy to address the global crisis of physical inactivity. It presents a roadmap for a more active, healthier, and sustainable future by outlining key challenges, targeted recommendations, and the role of relevant stakeholders. It was co-created based on multidisciplinary, international collaboration and guided through existing research and policy frameworks. Altogether, this symposium targets the sustainable development goals of ‘Good health and wellbeing (3)’ and ‘Reduced inequalities (10)’.